2021
DOI: 10.1038/s41577-021-00652-6
|View full text |Cite
|
Sign up to set email alerts
|

B cells in central nervous system disease: diversity, locations and pathophysiology

Abstract: B cells represent a relatively minor cell population within both the healthy and diseased central nervous system (CNS), yet they can have profound effects. This is emphasized in multiple sclerosis, in which B cell-depleting therapies are arguably the most efficacious treatment for the condition. In this Review, we discuss how B cells enter and persist in the CNS and how, in many neurological conditions, B cells concentrate within CNS barriers but are rarely found in the parenchyma. We highlight how B cells can… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
82
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 95 publications
(82 citation statements)
references
References 131 publications
(273 reference statements)
0
82
0
Order By: Relevance
“…Though relatively few B cells engraft and infiltrate the CNS compared to T cells, the possibility remains that engrafted EBV-specific or latently infected B cells may play a role through regulatory or non-antibody responses, such as cytokine production 62 and antigen presentation 63 . Engrafted B cells of varying specificities and functionalities, which can act both protectively and pathogenically in EAE 64,65 , may also contribute to the enhancement of disease and the increased CNS inflammation observed in RRMS recipient mice compared to HD groups. Clinical post-mortem evidence has suggested that EBV could contribute to the development and/or progression of MS through infection of CNS-infiltrating B cells and tertiary lymphoid structures, leading to local inflammation [66][67][68] .…”
Section: Discussionmentioning
confidence: 99%
“…Though relatively few B cells engraft and infiltrate the CNS compared to T cells, the possibility remains that engrafted EBV-specific or latently infected B cells may play a role through regulatory or non-antibody responses, such as cytokine production 62 and antigen presentation 63 . Engrafted B cells of varying specificities and functionalities, which can act both protectively and pathogenically in EAE 64,65 , may also contribute to the enhancement of disease and the increased CNS inflammation observed in RRMS recipient mice compared to HD groups. Clinical post-mortem evidence has suggested that EBV could contribute to the development and/or progression of MS through infection of CNS-infiltrating B cells and tertiary lymphoid structures, leading to local inflammation [66][67][68] .…”
Section: Discussionmentioning
confidence: 99%
“…B cells represent another important immune cell population that resides in the healthy meninges. B cells represent up to 30% of resident immune cells in the dura mater ( Brioschi et al., 2021 ; Cugurra et al., 2021 ; Fitzpatrick et al., 2020 ; Jain and Yong, 2021 ; Korin et al., 2017 ; Schafflick et al., 2021 ; Wang et al., 2021 ). Resident meningeal B cells exist in multiple stages of development, similar to those found in the bone marrow (e.g., mature naive B cells, immature B cells, pre-B cells, pro-B cells, and mitotic B cells) ( Brioschi et al., 2021 ; Schafflick et al., 2021 ; Wang et al., 2021 ).…”
Section: Meningeal Immune Landscapementioning
confidence: 99%
“…To recapitulate these observations in pre-clinical mice models, experimental autoimmune encephalitis (EAE) evoked by an injection of myelin proteins is commonly used. Both T and B cells are strongly implicated in MS (Chastain et al, 2011 ; van Langelaar et al, 2020 ; Jain and Yong, 2021 ). Self-reactive T cells in the choroid plexus support neuroimmune homeostasis in the CNS, but in MS and EAE, cerebrospinal fluid T cells skew toward a pathogenic T helper 17 (Th17) phenotype (Mundt et al, 2019 ) that are detrimental for brain function.…”
Section: Changes Following Cns Insultmentioning
confidence: 99%
“…In the cerebrovasculature, endothelial cells are also capable of antigen presentation in EAE and other chronic inflammatory conditions (Pinheiro et al, 2016 ). B cells in the dural meninges are also efficient APCs, and they accumulate and skew toward a pro-inflammatory phenotype in EAE (Jain and Yong, 2021 ). The diversity of cells that can serve as APCs (Chastain et al, 2011 ) highlight the complicated signaling cascades that underlie neuroinflammation in MS, but also serve as opportunities for therapeutic intervention.…”
Section: Changes Following Cns Insultmentioning
confidence: 99%